Active Learning Model in Geography Learning in Senior High Schools Indonesia (SMA Negeri Kuantan Tengah District) - Nawita, Yusri (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research was aimed to investigate and analyze the implementation of Active Learning model in Geography Learning in enior high schools in Indonesia (SMA in Kuantan Tengah District). The researcher employed a mixed method research, a combination of quantitatie and qualitative research method. The population of the research were all senior high schools in Kuantan Tegah District the is 3 senior high schools that were cosen through Cluster Random Sampling. Techniques of data analysis are(1) Quantitative analysis by using t testing. (2) qualitative analysis was following these steps: data selection and reduction, Data clarification, dapresentation, conclusionand verification. Based on the data analysis, in can be conluded : (1) The process of active learning model areintroducing the topics to the students, students were given time to search the materials from other references of they discuss with other peers about the given topics, teacher emphasize the explanation of the materials, dad finally, teacher conducted individual evaluation and give homeworks to students. (2)There was significant result obtained from learning using active learning model in Geography classroom in SMA Negeri in Kuantan Tengah District.